Student Response - Based Learning: A Strategy for Improving Student Participation in Learning - Karpin, Karpin; Mahmudatussa’adah, Ai (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2020)
In the context of 21st century learning, to achieve meaningful learning processes, one of the important elements is interaction. Student response - based learning can be used to actively involve students in the learning process. The study focused on stages of the learning process based on student responses and student responses to the learning. Formulation of the research problem is following: (1) how are the stages of the learning process based on student responses to increasing student participation in learning ?; (2) how is the student response to student response based learning? The research objectives are: (1) increasing the active participation of students in learning through conditioning the learning environment; and (2) describing the steps of the student response-based learning process. The research conducted is a research development. Conclusion of the results of the study: first, the stages of the student response-based learning process (learning model syntax) are (a) uploading teaching materials; (b) Question Individual Vote; (c) Peer Discussion; (d) Second Vote; (e) Whole-class Discussion. These learning steps can increase student participation in learning. Second, students generally give positive responses to student response based learning. A positive response is given to the factor of the variable (a) explanation; (b) facilitation; (c) value; (d) positivity; (e) distraction; and (f) participation.